ACADEMIC INTERACTION BETWEEN LECTURER AND CADETS IN ONLINE MARITIME ENGLISH CLASSROOMS: ITS IMPACT ON THE CADETS’ SPEAKING ABILITY - Nursyam; Nafsul Mutmainnah; Tjahjanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2023)
This study discussed the impact of academic interaction between lecturer and cadets in online classes on Maritime English subject. This research was conducted to determine the influence of academic interaction between lecturer and cadets on the cadets’ confidence to participate to speak in online classes of Maritime English subject. The study was conducted at Politeknik Pelayaran Barombong. Qualitative descriptive methods were used to obtain data and the data sources were 10 respondents. The instruments used in this study were indirect observation through video recordings, and interviews. The impacts of academic interaction on students’ confidence to participate in online EFL classroom in term of pronunciation, vocabulary, accuracy and fluency was in low category where most of the students had pronunciation problems, limited vocabulary, talks break up and stopped due to language limitation that make them combine English with Indonesian language.